2020
DOI: 10.1371/journal.ppat.1008131
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and distinct roles of CDPK family members in the pre-erythrocytic stages of the rodent malaria parasite, Plasmodium berghei

Abstract: Invasion of hepatocytes by Plasmodium sporozoites initiates the pre-erythrocytic step of a malaria infection. Subsequent development of the parasite within hepatocytes and exit from them is essential for starting the disease-causing erythrocytic cycle. Identification of signaling pathways that operate in pre-erythrocytic stages provides insight into a critical step of infection and potential targets for chemoprotection from malaria. We demonstrate that P. berghei homologs of Calcium Dependent Protein Kinase 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
(123 reference statements)
0
27
0
Order By: Relevance
“…CDPK4 conditional knockout mutants display a twofold decrease in productive invasion of HepG2 cells, and CDPK4 chemical inhibition leads to reduced sporozoite motility in P. berghei (Govindasamy et al, 2016). CDPK1 and CDPK5 also contribute to sporozoite gliding motility and host cell invasion, although increased cGMP can compensate for the functional loss of CDPK1 and CDPK5 during sporozoite invasion (Govindasamy & Bhanot, 2020). Disruption of CDPK6 gene in P. berghei caused an increase in sporozoite CT activity and reduced hepatocyte invasion, associated with a defect in CSP cleavage (Coppi et al, 2007).…”
Section: Signal Transduction In Plasmodium Sporozoites During Migration and Invasionmentioning
confidence: 99%
“…CDPK4 conditional knockout mutants display a twofold decrease in productive invasion of HepG2 cells, and CDPK4 chemical inhibition leads to reduced sporozoite motility in P. berghei (Govindasamy et al, 2016). CDPK1 and CDPK5 also contribute to sporozoite gliding motility and host cell invasion, although increased cGMP can compensate for the functional loss of CDPK1 and CDPK5 during sporozoite invasion (Govindasamy & Bhanot, 2020). Disruption of CDPK6 gene in P. berghei caused an increase in sporozoite CT activity and reduced hepatocyte invasion, associated with a defect in CSP cleavage (Coppi et al, 2007).…”
Section: Signal Transduction In Plasmodium Sporozoites During Migration and Invasionmentioning
confidence: 99%
“…Recent studies on in Plasmodium spp. have shown some overlapping functions of various CDPKs, which could have reduced the inhibitory effects of these potential CDPK inhibitors on in vitro parasite growth ( Blackman et al, 2020 ; Ghartey-Kwansah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In T. gondii , phosphorylation of MyoA is dependent on calcium and the calcium dependent protein kinase TgCDPK3 was identified as a kinase to phosphorylate serines in the N-terminus of MyoA (Tang et al , 2014; Gaji et al , 2015). Calcium is also important for activation of Plasmodium sporozoite motility (Carey et al , 2014) and three CDPKs have been shown to impact sporozoite motility with two influenced by protein kinase G (Govindasamy et al , 2016; Govindasamy & Bhanot, 2020). Our data showing that S19 phosphorylation is important during salivary gland invasion, migration in the skin and liver invasion, suggests that similar signaling pathways play a role at different steps during malaria transmission.…”
Section: Discussionmentioning
confidence: 99%